ANALYSIS OF FURNITURE DESIGN FOR GROWING CHILDREN BASED ON PHYSIOLOGICAL CHANGES IN CHILDREN - WEN, X.; PASHKEVYCH, K. L. (Art and Design, 2023)
The aim of this study is to determine the design needs and methods of children's furniture for growth from the perspective of children's physiology. Due to the current advocacy of sustainable design concepts, new structures and accessories can also meet the requirements of children's furniture design. At this stage, research on the design of growthable children's furniture is very important and timely. The study used the analysis of literature sources on the design of furniture, Comparative research method. Case analysis method, structural-functional analysis, synthesis of research results, etc. are used. Analyzing the design elements of growable furniture from the perspective of children's physiology, the types of furniture that can grow children are divided into three categories: children's desks and chairs, children's beds, and children's storage furniture. According to the requirements of children's human-machine ratio, it is determined that the height of children's desks and chairs can be adjusted, and the angle between the desktop and the back of the children's chair can also be adjusted. From an ergonomic point of view, these requirements are determined based on the child's height, weight and developmental characteristics. It is determined that through the standardized design, the children's bed can be disassembled or installed, the height of the bed can be changed, and the combination of the bed and other functions can also be satisfied. Determine the category of children's storage type furniture storage items, classify according to different items, and put forward requirements for the storage of different types of items. We explore the impact of children's physiological changes on children's furniture, meet the requirements of children of different ages for the use of furniture, at the same time, provide specific design ideas. The practical significance of the obtained results lies in the possibility of their application for designers and manufacturers in the design of children furniture.